THE INFLUENCE OF HALAL AWARENESS, RELIGIOSITY, AND SOCIAL MEDIA ON MUSLIM CONSUMERS' PURCHASE AND BOYCOTT DECISIONS - Retno Hernawati (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
This study investigates the influence of halal awareness and social media exposure on ethical consumption and boycott behavior among Muslim Generation Z in Kupang City, with religiosity serving as a moderating variable. Employing a quantitative research design, data were collected from 196 respondents using structured questionnaires and analyzed through multiple regression and Moderated Regression Analysis (MRA) with SPSS 27. The findings indicate that halal awareness and social media significantly and positively affect both ethical consumption and boycott behavior. Moreover, religiosity strengthens the relationships between halal awareness and consumption behavior as well as between social media exposure and consumption behavior. This suggests that individuals with higher levels of religiosity are more consistent in aligning their purchasing decisions with Islamic principles and moral considerations. The study theoretically contributes to the literature on Islamic consumer behavior by integrating religiosity as a moderating construct in explaining ethical consumption and boycott decisions among Generation Z Muslims. Practically, the findings provide insights for marketers, policymakers, and halal authorities in designing digital-based strategies to promote responsible and Sharia-compliant consumption.